THE IMPACT OF MIGRATION POTENTIAL ON THE DEVELOPMENT OF MUTUALLY BENEFICIAL RELATIONS BETWEEN UZBEKISTAN AND THE BENELUX COUNTRIES - Tursunova Shakhnoza Ashrafovna (PEDAGOGS, 2024)
The article provides statistical data on the visits of Benelux residents to Uzbekistan during 2018–2022 and highlights the main areas of cooperation between the countries under consideration.